Molecular phylogenetics provides a novel hypothesis of chromosome evolution in Neotropical fishes of the genus Potamorhina (Teleostei, Curimatidae) - Dorini, Beatriz F. [UNESP]; Ribeiro-Silva, Luís R. [UNESP]; Foresti, Fausto [UNESP]; Oliveira, Claudio [UNESP]; Melo, Bruno F. [UNESP] (Hindawi, 2020)
Potamorhina includes the largest species in the Neotropical fish family Curimatidae. They perform long-distance migrations in large schools and represent relative importance for regional fisheries in South American lowlands. A morphology-based phylogenetic study recognized five species and proposed interspecific phylogenetic relationships mostly based on osteology, squamation, and morphology of the gasbladder. Subsequent cytogenetic studies revealed extreme variability in diploid numbers and other cytomolecular structures and hypothesized multiple events of chromosome rearrangements with centric fissions followed by reversed fusions. However, neither the taxonomic revision and phylogeny nor the cytogenetic hypothesis of chromosome evolution in Potamorhina was tested using molecular phylogenetic approaches. Here, we use mitochondrial and nuclear DNA sequences to delimit species of Potamorhina with an extensive sampling across the Amazon basin and use phylogenetic methods to test prior hypothesis of multiple events of chromosome rearrangements during the evolution of the genus. Phylogenetic and species delimitation methods clearly support the presence of five species but reveal novel interspecific relationships allowing a reinterpretation of the morphological characters relative to the number of vertebrae, caudal peduncle pigmentation, and modifications in the gasbladder chambers. With the new phylogenetic arrangement, we propose a novel hypothesis of occurrence of a single chromosome fission in the lineage of P. latior followed by an extraordinary event that involved more than 20 chromosome-pair fissions during the evolution of the ancestor of P. altamazonica and P. squamoralevis. This novel hypothesis represents a simpler and more conceivable explanation for the achievement of these elevated chromosome numbers during the evolution of Potamorhina.
Keywords: Characiformes; cytogenetics; morphology; Ostariophysi; systematics